Correlation between the Leg Length, Leg Muscle Explosive Power, Speed, and Body Mass Index (BMI) towards the Outcomes of Kids Athletics - Budiyanto, Agus; Amat Komari (UNIB Press, 2025)
This research aims to determine the correlation between leg length, leg muscle explosive power, speed, and body mass index towards kids athletics outcomes of male fourth grade students in elementary schools of Cluster 2, Gantung District, East Belitung Regency. This research was a quantitative study with correlational research. Instruments for measuring leg length with anthropometry, leg muscle explosive power with standing broad jump, speed with 20-meter sprint, body mass index was measured by the formula for dividing body weight (kg) by the square of height (m2) and kids Athletics outcomes using 4 tests: turbo throw, frog jump, kanga escape, and formula one. The research findings reveal that: (1) there is a significant correlation between the Leg length with the outcomes of kids athletics, the calculated ρ value is at 0.313 > ρ table 0.216 and the p-value is at 0.004 < 0.05; (2) there is a significant correlation between the explosive power of the leg muscles with the results of kids athletics, the calculated ρ value is at 0.826> ρ table at 0.216, the p-value is at 0.000 < 0.05; (3) there is a significant correlation between the speed with the results of kids athletics, the calculated ρ value is at 0.782 > ρ table 0.216, the p-value is at 0.000 < 0.05; (4) there is a significant correlation between the body mass index with the results of kids athletics, the calculated ρ value is at 0.525 > ρ table 0.216, the p-value is at 0.000 < 0.05; and (5) there is a significant correlation between leg length, leg muscle explosive power, speed and body mass index with the outcomes of kids athletic with a calculated F value of 79.563 > F table (df 4; 78) 2.49 and a significance value of p-value 0.000 < 0.05.